Needle aspiration as therapeutic management for suppurative cervical lymphadenitis in children - Mee Young Baek; Kyung Hee Park; Ju Hee We; Su Eun Park (Korean Pediatric Society, 2010)
PurposeThis study aimed to evaluate the usefulness of the needle aspiration alternative to open surgical drainage of children with suppurative cervical lymphadenitis requiring surgical drainage.MethodsFrom January 1998 to June 2008, we retrospectively reviewed 38 children treated with needle aspiration as management with suppurative cervical lymphadenitis instead of open surgical drainage.ResultsAll 38 children underwent only 1 puncture. Two patients (5.2%) out of 38 patients experienced reformation of an abscess and all recovered completely after re-treatment with antibiotics. Minor complications were detected in 2 patients (5.2%). One complication originated from remnant necrotic tissue and the other involved formation of a small scar in two patients, which resolved spontaneously. There were no major complications.ConclusionNeedle aspiration can be a simple, safe, and effective alternative procedure to open surgical drainage of children with suppurative cervical lymphadenitis requiring surgical drainage.